Budaya Organisasi, Kompetensi Dan Kinerja Karyawan Pada PT. Angkasa Pura II (Persero) Kantor Cabang Bandar Udara Sultan Syarif Kasim II Pekanbaru - Raden Lestari Garnasih (Forum Manajemen Indonesia (FMI), 2014)
This study aims to determine how the variables influence organizational culture and competencies on the performance of employees at PT Angkasa Pura II (Limited) Branch Airport Sultan Syarif Kasim II Pekanbaru. This study uses primary data is data obtained from interviews and questionnaires giving to all employees at PT Angkasa Pura II (Limited) Branch Airport Sultan Syarif Kasim II Pekanbaru. Secondary data relating to the object and organizational structure. The population is the entire workforce of about 291 employees and 74 employees were sampled. The method of analysis used in this study is the method of multiple linear regression. From the results of testing that has been done, the results of the partial test (t test) showed that the variables of organizational culture and competence partially significant effect on employee performance. The results of the calculation of the coefficient of determination (R2) is equal to 0.538 which means that the culture of the organization and competence variables jointly affect the performance of employees by 53.8%, while the remaining 46.2% is influenced by other variables were not examined in the study this. Keywords: organizational culture, competencies, and employee performance